Non Shock Dynamic Compression of Tantalum - Partom, Yehuda (European Journal of Applied Sciences, 2021)
We start by simulating the response of tantalum to dynamic non-shock loading using a standard hydrocode, and the results we get are not consistent with test data. Standard hydrocodes use what we call the flowstress approach to describe the dynamic viscoplastic response of materials. We therefore transform our hydrocode to use what we call the overstress approach to dynamic viscoplastic response. It turns out that using the overstress approach makes the hydrocode more successful in reproducing non-shock dynamic compression test data.